Accountability of directly observed treatment (DOT) for tuberculosis in lower part of Southern Thailand (Region 12) : interrelationship between DOT observer in practice, compliance to the DOT principle, and treatment outcomes - Petchawan Pungrassami (Prince of Songkla University, 2022)
Thesis (Ph.D., Epidemiology)--Prince of Songkla University, 2001